Numerical study of flow in diffuser- Investigation with three turbulence models and comparison with experimental data - ROGESTEDT, JOHAN; Zaben, Mohamed; Forsell, Martin (My University, 2018)
Fluid dynamics is a branch of physics that has many applications when it comes to solving real-world problems. Areas that utilise the knowledge in fluid dynamics in order to develop technology that is more efficient and less resource craving are diverse and range from the energy sector to the transport sector. Furthermore, as computational power increases, it becomes both more cost- and time effective to move from conducting practical experiments to instead perform numerical computer simulations.This project has studied the possibility of conducting numerical simulations of the separation phenomenon and also if it is possible to capture the effects of flow control meant to minimise separation. More specifically this thesis has focused on the case with flow through a conical diffuser with an annular inlet and a center body present, where the center body causes the flow to separate. This center body before the diffuser part could in practical applications be in the form of a bearing hub. Separation is usually an undesirable feature for flows in confined space and the ability to counteract its development through both passive (geometrical alterations) and active (for example injection of jets) flow control mechanisms are important tools to an optimised diffuser design. The availability of the well performing open source program such as OpenFOAM is a further reason to why the development of accurate numerical methods is of particular interest. The simulations undertaken in this project has produced results in the form of three component mean velocity distributions of the flow in a conical diffuser with an annular inlet and center body present. Results were then compared with experimental reference data. The investigation covered three turbulence models (k-!, k-!-SST and k-!-SST-SAS) in two different geometries, corresponding to the implementation of a passive separation control feature by implementing a straight section after the center body (in order to minimise separation and in accordance with reference experiment for comparison). Additionally, the effect of a flow control method called Coanda blowing in order to minimise separation was thoroughly investigated. A swirl component of the inlet velocity in order to increase pressure recovery was another implementation made and compared to reference data. The results showed that the k-! and k-!-SST models managed to capture the general motion of the flow with and without passive flow control. However, the Coanda effect from the jets proved difficult to capture, even when a refined mesh was created. The k-!-SST-SAS model proved ineffective here, despite its said superiority in previous experiments. Probably, lack of previous experience in CFD simulations as well as higher mesh demands for the SAS model explains its poor results. The results, however, validated the proposed coupling between separation in the wake and in the wall boundaries as well as how swirl can generate an increased pressure recovery.
Keywords: Akustik; Hållbar utveckling; Energi; Acoustics; Sustainable Development; Energy